Faktor-Faktor Yang Berhubungan Dengan Gejala Insomnia Pada Siswa Menengah Atas - Muhammad Alamsyah Nasution; Retno Mardhiati; Dian Kholika Hamal (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2022)
Insomnia is an event where a person has trouble sleeping even though he has enough time to sleep. Common symptoms of insomnia are difficulty falling asleep, difficulty maintaining sleep and waking up early in the morning. The goal of this study was to determine the factors associated with insomnia symptoms in students of Senior High School. This type of research is a quantitative study with a cross-sectional study design. The population in this study were all students at SMAN 13 Tangerang City in 2022. The sampling technique used Quota Sampling with a total sample of 250 students. The data collection used was a questionnaire in the form of a questionnaire in July 2022. Data were analyzed univariately and bivariately using the Chi Square Test. Univariate results for the most categories showed a relationship between gender (Pvalue 0.003), exercise habits (Pvalue 0.00001), stress level (Pvalue 0.004) and insomnia symptoms. In conclusion, there is a relationship between insomnia symptoms and gender, exercise habits, and stress levels.